Complex nature of serum lysozyme activity: evidence of thermolability in inflammatory bowel disease. - Ward, M (1978)
In patients with Crohn's disease and ulcerative colitis, alterations in serum storage temperature produced significant changes in serum lysozyme activity (SLA) as measured by the lysoplate method. This was not the case in healthy controls or in a group with other gastrointestinal disorders. Electrophoretic separation of serum revealed two components of lysozyme-type lytic activity but only one in extracts of gut mucosa, leucocytes, and egg white. The major lytic component of serum migrated towards the cathode and reacted with specific antilysozyme serum, but the minor component which migrated towards the anode did not. Although the cause of this anionic lytic activity is uncertain, it contributes to total serum activity as estimated by any method utilising the lysis of Micrococcus lysodeikticus, and may possibly be related to the observed thermolability.